Propriedade fotocatalítica de SrSnO3 e derivados: eficiência na degradação de corantes, otimização nos parâmetros de reação e avaliação toxicológica - Honorio, Luzia Maria Castro (2018)
Strontium stannate, SrSnO3, is a perovskite of the orthorhombic type that presents several technological applications due to its interesting physical and chemical characteristics, being quite used as a photocatalyst. In this work, SrSnO3 and derivatives (SrSnO3: Cu2+, SrSnO3@ZrO2, SrSnO3: Cu2+@ZrO2) were obtained by modified Pechini method, characterized by X-ray diffraction (XRD), infrared (IR) spectroscopy UV-visible spectroscopy, Raman spectroscopy, specific surface area (BET), photoluminescent emission spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), dispersive energy spectroscopy (EDS) with mapping, applied in the photocatalytic evaluation of synthetic dyes. The target molecules chosen were yellow gold remazol (RNL), methylene blue (MB) and eosin (EA), being compounds generally found in wastewater and industrial waters. The photocatalytic tests using the RNL azaser were performed in a reactor using three 9W UVC lamps (λ = 254 nm) in order to determine the participation of each reactive species from the use of hydroxyl radicals, holes and electrons in the oxidation of the dye. On the other hand, the tests using the MB and EA dyes had the optimized operating parameters (such as the photocatalyst concentration, solution pH, presence of inorganic salts, presence of radical scavengers and light source) quantified and monitored by coupled liquid chromatography to the masses for identification of degradation products after the photocatalytic process. Stability by cycle reuse and toxicity evaluation of the solutions before and after the photocatalytic process were done by toxicity tests using saline artemia and the MTT test using the last two dyes. The results of the photocatalytic evaluation showed that SrSnO3 and SrSnO3@ZrO2 photocatalysts obtained excellent degradation percentages in all dyes under UV radiation, and that performance was improved for SrSnO3@ZrO2 assigned to the synergy of the positions of the energy bands that suppress the electron recombination / hole and consequently lead to the generation of oxidative species and final conversion of the dyes. In addition, the action of isopropyl alcohol promoted a considerable inhibition indicating that the participation of the species • OH is extremely important in the degradation process and its oxidations occur through an indirect mechanism. In particular, in the MB and EA dyes, these data were more significant since, after successive cycles of reuse, these compounds ensured stability greater than 50% degradation compared to the percentages obtained in the initial cycles. The toxicity tests showed positive results thus reinforcing that the degradation products exhibited a lower toxicity level than the starting solution in the case of brine shrimp, thus guaranteeing benefits, since the solutions of the dyes before treatment were colored and after process the same have become transparent and / or colorless with toxic negative effect compared to the initial solutions. Finally, the importance of the optimization of the operational parameters in order to guarantee success and cost / benefit for future applications is emphasized.